1989
DOI: 10.1002/gps.930040605
|View full text |Cite
|
Sign up to set email alerts
|

Family history of depression and alcoholism in Alzheimer patients and age‐matched controls

Abstract: SUMMARYDepression and depressive symptoms are reported to occur frequently in patients with Alzheimer's disease; however, familial and psychobiological contributions associated with depression in Alzheimer patients are poorly understood.In this study, we compared family history of depression and alcoholism in 44 patients with probable Alzheimer's disease and 38 aged-matched cognitively intact controls. Results from comparison showed no overall difference between the occurrence of depression in first-degree rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A secondary, unexpected result of the present study was the reduced risk of anxiety disorders and substance abuse in first-degree relatives of AD patients in comparison with relatives of controls.A lower risk of alcoholism in relatives of AD subjects had already been described by Lawlor et al (1989).…”
Section: Discussionmentioning
confidence: 86%
“…A secondary, unexpected result of the present study was the reduced risk of anxiety disorders and substance abuse in first-degree relatives of AD patients in comparison with relatives of controls.A lower risk of alcoholism in relatives of AD subjects had already been described by Lawlor et al (1989).…”
Section: Discussionmentioning
confidence: 86%
“…Devi et al (2004) found preliminary evidence of a higher prevalence of a history of psychiatric symptoms among relatives of EOAD patients when compared to LOAD patients. Some earlier studies (Martin et al, 1988;Lawlor et al, 1989;Li et al, 1992;van Ojen et al, 1995;Fahim et al, 1998) have shown increased occurrence of depression and other psychiatric disorders among the relatives of patients with AD. Other studies (Pearlson et al, 1990;Strauss and Ogrocki, 1996) reported an increase in depression among relatives of probands with AD, specifically when the latter had co-morbid depression.…”
Section: Introductionmentioning
confidence: 96%
“…Few studies have examined the familial aggregation of AD and depression simultaneously. The available studies [32][33][34][35][36] have often shown increased occurrence of depression and other psychiatric disorders among the relatives of patients with AD, and vice versa. Two groups 37,38 reported an increase in depression among relatives of probands with AD, specifically when the latter had comorbid depression.…”
mentioning
confidence: 99%